Radiocarbon data of microfossils from sediment core PS51/159-10 - Lin, Tsai-Wen; Grotheer, Hendrik; Wollenburg, Jutta Erika; Mollenhauer, Gesine (In: Lin, Tsai-Wen; Tesi, Tommaso; Hefter, Jens; Grotheer, Hendrik; Wollenburg, Jutta Erika; Mollenhauer, Gesine (2025): Bulk organic matter δ13C, biomarker, and microfossil radiocarbon data of cores PS51/154-11 and PS51/159-10 from the Laptev Sea, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.980076, 2025)
The data include additional radiocarbon measurements on microfossils from core PS51-159-10, which were used to establish an age-depth model. Sediments were wet-sieved through a 63 μm mesh, and shell fragments were picked from the > 63 μm, oven-dried sediment fraction and examined under a microscope for species identification. Radiocarbon measurements were conducted using the MIni CArbon Dating System (MICADAS) accelerator mass spectrometer at Alfred Wegener Institute (AWI) (Mollenhauer et al., 2021).
Keywords: 13C; 14C; Arctic Ocean; Biomarker; Fatty acid; Laptev Sea; Lignin phenols; MAR; Marine sediment; Marine Sediment Core; Mass accumulation rate; n-alkane; Radiocarbon dating